Clinical decision support menu for reducing unnecessary urine cultures - Erik Stensgard; Bobbie Masoud; Amy Gravely; Dimitri Drekonja (Cambridge University Press, 2024)
A clinical decision support menu requiring selection of urine culture (UC) indication within outpatient and inpatient settings of a large integrated health care system significantly reduced UC sample collection. Clear documentation of selected UC indication in most post-intervention cases affirms its potential as an effective diagnostic stewardship strategy.